Anxiety and Pain Severity in Children Based on Self-Report - Mirmotalebi, Maryam; Garrusi, Behshid; Danaei, Mina (International Journal of Child Health and Nutrition, 2021)
Background and Objective: Evaluation of the severity of pain in children can help the medical team diagnose the type of disease. In this study, anxiety and pain intensity in children were examined based on self-report. Materials and Methods: This cross-sectional study was performed in 2018 on 300 children aged 3 to 12 years, referring to outpatient treatment centres in Kerman. To measure the severity of pain felt by children, FPS-R was used. The level declared by children was evaluated by the pain intensity estimated by parents and doctors using a visual analogue scale (VAS) and the standard FLACC (Face, Legs, Activity, Cry, Consolability scale) for correlation. The data were analysed using SPSS software version 25. Results: The pain reported by children was obtained by VAS (4.16 ± 3.49), and the estimated pain by the doctor was obtained by FPS-R (2.87±1.68). The pain severity estimated by the doctor using FLACC had the highest correlation with the pain estimated by the doctor using VAS and the lowest correlation with the pain estimated by the mother using VAS. Conclusion: The results of this study showed that FPS-R could be used as a suitable self-report tool in children and, along with the standard FLACC, can help the medical team recognize the severity of children's pain.